Clinical Debrief: learning and well‐being together. (15th July 2019) - Farrington, Rebecca; Collins, Lisa; Fisher, Pip; Danquah, Adam; Sergeant, Jamie
Summary: Background: Clinical environments can be so stressful to medical students as to be detrimental to their learning and well‐being. Our intervention, Clinical Debrief, integrates learning through clinical experience with the development of positive coping strategies. Students shared cases and experiences during weekly small group classroom discussions, facilitated by general practitioners (from outside their current hospital placement), throughout two consecutive 12‐week blocks of their first clinical year. Alongside enquiry‐based and clinical reasoning learning, we gave students a safe space to reflect on their affect. Our aim was to critically examine students' views in Clinical Debrief. Method: Anonymised quantitative and qualitative evaluation data were collected over 3 years using online questionnaires on completion of each 12‐week block. The data relating to psychological supervision were analysed independently and in parallel, using thematic analysis for qualitative data. We aim to help students develop positive coping mechanisms, promoting empathy, self‐awarenessand wellbeing Results: A total of 1857 evaluations were extracted (response rate 67%). The median (interquartile range) overall rating for Clinical Debrief sessions was 9 (8–10), where 10 indicates 'excellent' and 1 indicates 'significant improvement needed'. The rating for the supervisory aspects of the sessions and free‐text comments were positive. Students appreciated safe environments, the session structure, facilitator role modelling, transitional support and processing of emotional experiences. Discussion: Mandatory integrated longitudinal supervision, using trained clinician facilitators, was positively received by students in transition to clinical placements. Normalising the emotional impact of medical work destigmatises distress. Linking clinical reasoning with affective state awareness to contextualise case management, following Mezirow's transformative learning theory, brings added benefit to learning and well‐being. Student demand for the expansion of Clinical Debrief is evidence of success.